DAYA GUNA SINBIOTIK DALAM TATA LAKSANA DIARE AKUT ROTAVIRUS PADA ANAK - , Made Ratna Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Diarrhea is one of major causes of morbidity and mortality in children throughout the world and rotavirus is the main cause. Management of acute diarrhea that is use in daily practice currently is the WHO five steps diarrhea management. Synbiotic therapy is reckon to shorten the duration of diarrhea. Aim of this study was to compare the duration of acute rotavirus diarrhea between synbiotic compared to placebo group. This study was a double blind randomized controlled trials in children aged â¥6 months-â¤59 months infected with rotavirus in Pediatric Gastrohepatology Division in Denpasar. Rotavirus was detected through immunochromatography assay. Kaplan-Meier survival analysis was used to predict the effect on the duration of diarrhea. Analysis of covariance (general linear model) was used to determine other factors that affect the duration of diarrhea in addition to the treatment given. Significance level was 0.05. The median duration of diarrhea among the synbiotic group was 50.0 hours (SE 1.1) (95% CI 47.9 to 52.1) and the placebo group was 63.0 (SE 5.9) (CI 95% 51.4 to 74.6). Based on Kaplan-Meier survival rate, duration of diarrhea among the synbiotic group was shorter than placebo group (log-rank test P <0.0001). Based on the analysis of covariance (general linear regression) proved that the treatment had a strong influence on the duration of diarrhea.